2022
DOI: 10.3389/ti.2022.10134
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes as Endpoints in Clinical Trials of Kidney Transplantation Interventions

Abstract: Patient-reported outcomes (PROs) that assess individuals’ perceptions of life participation, medication adherence, disease symptoms, and therapy side effects are extremely relevant in the context of kidney transplantation. All PROs are potentially suitable as primary or secondary endpoints in interventional trials that aim to improve outcomes for transplant recipients. Using PRO measures (PROMs) in clinical trials facilitates assessment of the patient’s perspective of their health, but few measures have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Importantly, a more diverse staff also helps patients from minority backgrounds to feel better valued during their hospital stay. In fact, it is not uncommon to observe—because of religious and sociocultural beliefs—challenges for women to be assisted by male doctors or associated staff; therefore, to have an impact on patient health outcomes and quality of life, the care the same patients experience and how they perceive their representation is essential [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a more diverse staff also helps patients from minority backgrounds to feel better valued during their hospital stay. In fact, it is not uncommon to observe—because of religious and sociocultural beliefs—challenges for women to be assisted by male doctors or associated staff; therefore, to have an impact on patient health outcomes and quality of life, the care the same patients experience and how they perceive their representation is essential [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that patients listed for re-transplantation are a selected population deemed capable of receiving another graft, it seems likely that those who are not relisted (primarily because of comorbidity and unacceptable risk) will have worse outcomes on dialysis. In addition, none of these analyses considers the burdens of returning to dialysis after failed transplantation, such as the costs associated with treatment ( 27 ), decreased ability to work and participate in society ( 28 ), and the psychological impact of returning to dialysis ( 29 31 ) (see also article by Tong et al on patient reported outcome measures, in this Special Issue ( 32 )).…”
Section: Rationale For Cma Applications For Late Graft Failurementioning
confidence: 99%
“…[1][2][3] Previous research demonstrated that receiving a KT is associated with many benefits post-transplant, 4 including improvements in QOL. 5,6 An unexplored period in ESKD patients' clinical experience is the KT evaluation (KTE) process. It is a period with many demands and stressors placed on a patient, which may lead to poorer patient-reported outcomes (PROs), including poorer QOL and low satisfaction with care.…”
Section: Introductionmentioning
confidence: 99%
“…It reduces mortality, improves quality of life (QOL), and costs less than dialysis 1–3 . Previous research demonstrated that receiving a KT is associated with many benefits post‐transplant, 4 including improvements in QOL 5,6 . An unexplored period in ESKD patients’ clinical experience is the KT evaluation (KTE) process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation